Effectiveness of harmonic scalpel in patients submitted to total thyroidectomy: systematic review with meta-analysis - Aires,Felipe Toyama (2018)
SUMMARY OBJECTIVE: The objective of this study was to evaluate the efficacy and safety of the harmonic scalpel compared to the conventional technique in patients submitted to total thyroidectomy. METHOD: This is a systematic review with inclusion of randomized controlled trials (RCTs) that compared both techniques. An electronic search was carried out in the Medline and Lilacs databases until June 2017. The outcomes analysed were operation time, intraoperative bleeding, surgical morbidity, and costs. RESULTS: Data from 31 primary studies were included. The use of the harmonic scalpel correlates to a shorter operation time (p <0.001) and a lower volume of intraoperative bleeding (p <0.001). There were no differences in the risk of transient (p = 0.53) and permanent (p = 0.70) hypocalcaemia, transient (p = 0.61) and permanent (p = 0.50) dysfunctions of the inferior laryngeal nerve and hematoma (p = 0.14). CONCLUSION: Total thyroidectomy using a harmonic scalpel is effective and safe compared to the conventional technique.